2014
DOI: 10.1002/jclp.22146
|View full text |Cite
|
Sign up to set email alerts
|

Parental Relationships and Behavioral Approach System Dysregulation in Young Adults With Bipolar Disorder

Abstract: Strain in parental relationships may be associated with BAS dysregulation for individuals with bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It has been proposed that self-criticism can be viewed as an outcome of insecure attachment 12 , given associations between insecure attachment styles and heightened self-criticism 13 15 . Moreover, individuals who recall their parents as critical 16 , rejecting 17 and overprotecting 15 are much more likely to be self-critical in contrast to those who are able to recall parental warmth 15 . Previous research has also explored neurophysiological (fMRI) responses in subjects who recalled high and low criticism from their mothers 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that self-criticism can be viewed as an outcome of insecure attachment 12 , given associations between insecure attachment styles and heightened self-criticism 13 15 . Moreover, individuals who recall their parents as critical 16 , rejecting 17 and overprotecting 15 are much more likely to be self-critical in contrast to those who are able to recall parental warmth 15 . Previous research has also explored neurophysiological (fMRI) responses in subjects who recalled high and low criticism from their mothers 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It is probable that bipolar patients tend to experience higher level of emotional expression and negative selfassessment, in this sense, when they face negative feedback from family members; they experience higher level of negative emotions [37].…”
Section: Discussionmentioning
confidence: 99%
“…A similar result occurred in the between-group analyses. According to the literature, BD caregivers present low scores of self-esteem (Muralidharan, Kotwicki, Cowperthwait, & Craighead, 2015), probably due to negatively perceived global stigma, which is negatively correlated to self-esteem (Chien et al, 2014). Not many studies that evaluate self-esteem and quality of life in the family were found.…”
Section: Discussionmentioning
confidence: 99%